The Use of Integrase Strand Transfer Inhibitors to Treat HIV in Pregnancy. (24th June 2021) - Nissim, Oriel; Lazenby, Gweneth B.
Abstract: For pregnant women with HIV, antiretroviral therapy (ART) plays a key role in prevention of perinatal transmission. Newer antiretroviral regimens now contain integrase strand transfer inhibitors, which have been found to rapidly suppress HIV viral load in nonpregnant women; however, there are limited data for use in pregnancy. Here, we present the case of a pregnant woman with well‐controlled HIV on a well‐tolerated prepregnancy regimen of bictegravir, emtricitabine, and tenofovir alafenamide. As there are limited safety data on bictegravir in pregnancy, this ART regimen was changed to a preferred regimen for pregnancy. In the second trimester, because of adverse effects from the new ART regimen and after a risk‐benefit discussion, the patient restarted the original regimen. She was able to maintain viral suppression until giving birth.